Rasulullah Sebagai Pendidik; Studi Tematis Hadis Perspektif Morfosemantik dan Didaktik - Tafiati Tafiati; Maksum Maksum; Khoiriah Khoiriah; Novizal Wendry (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This paper aims to reveal the profile of Muhammad SAW as an educator. The success of the Prophet in building Arab from an ignorant society to a world-class civilized society invites questions about the characteristics and professionalism of the Prophet as an educator. The study was conducted on several related hadiths, using morphosemantic and didactic linguistic approaches. Specifically, to reveal the characteristics of the Prophet as an educator, it will be traced through hadiths that explicitly contain the phrase Rasulullah as an educator. Meanwhile, related to professionalism, it is traced through the hadiths that describe the method of education practiced by the Prophet. This study found that; 1) There are three characteristics of the Prophet as an educator seen explicitly in the hadith, namely; a) mu'allim muyassir, b) ahsanu ta'lim, and c) arfaqu mu'allim. 2) The Prophet practiced various methods in education/learning and used the correct method for particular learning, as the professional form of the Prophet as an educator